The Deployment of Drones in Sending Drugs and Patient Blood Samples COVID-19 - Anggraeni, Sri; Maulidina, Aulia; Dewi, Mauseni Wantika; Rahmadianti, Salma; Rizky, Yulian Putri Chandra; Arinalhaq, Zulfa Fathi; Usdiyana, Dian; Nandiyanto, Asep Bayu Dani; Al-Obaidi, Abdulkareem Sh. Mahdi (Universitas Pendidikan Indonesia, 2020)
At present, most countries all over the world are being hard hit by the COVID-19 pandemic and some even are being hit harder than others. This condition has caused widespread disruption of the economic, social, and educational systems in those countries. Â Under these conditions, transportation systems also need to be considered. There are problems of distribution of drugs and kits of test equipment to areas far from large cities in the center of the corona pandemic due to access difficulty. Remote locations, being difficult to reach, make the distribution of drugs and equipment for rapid testing uneven so that the recovery rate of patients in the area has a low percentage. Meanwhile, it is essential to ensure the availability of drugs and rapid test equipment in every public health center in all directions of Indonesia. One possible solution is the use of drones to distribute these things to areas that are difficult to reach. This solution is expected to at least improve healing and reduce mortality for patients infected with COVID-19 in remote areas.